2021
DOI: 10.30901/2227-8834-2021-3-63-73
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genotype × environment interactions and assessment of the adaptability potential in barley under the conditions of the Northern Trans-Urals

Abstract: Background. Crop yield is a compound and complex character in breeding programs. A stable high yield is determined by the genotype, environmental impacts, and their interaction. A comprehensive assessment of cultivars based on their adaptability, plasticity and stability makes it possible to select among the studied assortment the most promising, potentially high-yielding and environmentally flexible plant forms adaptable to a wide range of environmental conditions.Materials and methods. Evaluation of 146 acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…As far as the authors are concerned, there are no publications on the possibility of using these coefficients for evaluating herbaceous raw material crops. It was shown that similarly to grain crops [17], genotypes with linear regression coefficient (b i ) greater than 1 and variance of deviations from the regression line (σd 2 ) tending to 0 were classified as valuable genotypes by yield of fresh material, mass fraction of essential oil and essential oil yield [25]. In terms of the most valuable characteristic for essential oil-bearing oregano, the essential oil areal yield, the collection local genotype No.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the authors are concerned, there are no publications on the possibility of using these coefficients for evaluating herbaceous raw material crops. It was shown that similarly to grain crops [17], genotypes with linear regression coefficient (b i ) greater than 1 and variance of deviations from the regression line (σd 2 ) tending to 0 were classified as valuable genotypes by yield of fresh material, mass fraction of essential oil and essential oil yield [25]. In terms of the most valuable characteristic for essential oil-bearing oregano, the essential oil areal yield, the collection local genotype No.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the long-term data analysis, the coefficient of ecological variation (Cv ecol ) makes it possible to assess the ecological stability and ecological influencing factors, as well as to determine the adaptivity of genotypes [28]. Its effectiveness has been shown for grain crops [25,29]. However, to assess the studied economically valuable characteristics of oregano, this coefficient was not sufficiently indicative with respect to other calculated parameters reflecting the ecological adaptability to the conditions of the region.…”
Section: Discussionmentioning
confidence: 99%
“…Описаны результаты, дающие косвенное подтверждение как повышению уровня урожайности сортов зерновых культур при селекции на повышенный уровень стабильности по данному признаку, так и его снижению. В пользу первого говорят отмеченные существенные корреляционные связи между средней урожайностью образцов ячменя и показателями их пластичности (отрицательные) и стабильности (положительные) по этому признаку для условий Северного Зауралья (Tetyannikov, Bome, 2021). В пользу второго свидетельствуют данные выполненных опытов с яровой пшеницей, в которых показана отрицательная взаимосвязь между средней величиной урожайности зерна и ее стабильностью в разных условиях выращивания (Du et al, 2020).…”
Section: Introductionunclassified